STUDI DAMPAK PENGGUNAAN KENDARAAN BERMOTOR OLEH WISATAWAN MUSEUM POS INDONESIA DAN KEBUN BINATANG BANDUNG BERDASARKAN EMISI CO2 YANG DIHASILKAN TERHADAP RUANG TERBUKA HIJAU DI KOTA BANDUNG - Novie Puji Astuti, Amelia
One of characteristic of city development can be seen from the number of visits which head to city area. Increasing of the number of visits also can be seen by the increasing of vehicle use. Bandung, one of metropolitan city who has the increasing of vehicle use. It can be seen by the increasing trend of vehicle use which entered Bandung through the highway from 5 toll booths entering at Bandung City, that is y=28.743.313,71 + 1.149.630,75x (Analysis Data, 2015). As well as happened to increasing of vehicle use by the tourist who visited Bandung City is caused by the possibility of increasing of number of tourists who travel to tourism destination at Bandung City. However the increasing of vehicle use has potential impact to increase CO2 emission to the air. This research has aim to identify number of impact that will be accepted by the green space at Bandung City as the absorbent of CO2 emission gasses which produced from the vehicle use by the tourists who travel to Museum of Pos Indonesia and Bandung Zoological Park. Total sample that used are 50 samples at each tourism destination with questionnaire spreading method. The method that used to process and analysis data is description quantitative method with the application of ecological transportation footprints concepts, which is consist of physic ecological footprints and carbon footprints to calculateCO2 emission. After that the next step was analyzing to know the ecological condition of Bandung City area. Analysis data shown that number of physic ecological footprints is 75,84 ha. Total emission that produced from the vehicle use by the tourists who travel to both of the tourism destination was 4.051.109,68 kg/year, with total 83.775,14 kg/year produced from the vehicle use by the tourists of Museum of Pos Indonesia and total 3.967.334,54 kg/year from the vehicle use by the tourists of Bandung Zoological Park. The ability to absorb by the green space at Bandung City was 19.349,90 ton/year so that the whole of emission CO2 had produced can absorb, which is equal with 20,94% ability of absorb by the exists green space. Based on results of the research, was indicating that at this time Bandung City has criteria of ecological reverse, where total productive land still exceed if compared with total ecological transportation footprints that produced..